The complete mitochondrial genome of Helophilus virgatus (Diptera: Syrphidae: Eristalinae) with a phylogenetic analysis of Syrphidae - Hu Li; Juan Li (Mitochondrial DNA. Part B. Resources, 2019)
The complete mitochondrial genome (mitogenome) of Helophilus virgatus (Coquilletti, 1898) was sequenced. Its whole mitogenome was 15,742 bp in length, and all 37 genes were in the ancestral gene arrangement. ATN was used as start codon in most of PCGs except for ND1 and COX1, which used TTG. Besides, ATP8, ND3, ND5, and ND6 ended with an incomplete T, the others used TAA as termination codons. A phylogenetic tree based on 13 PCGs from 14 species (11 Syrphidae and 3 outgroup species) shows that Syrphinae and Eristalinae form a sister group, and supports the monophyly of Syrphidae.